The Launch of the European Patients' Academy on Therapeutic Innovation in the Netherlands: A Qualitative Multi-Stakeholder Analysis - van Rensen, Annemiek; Voogdt-Pruis, Helene R; Vroonland, Eva (Frontiers in Medicine, 2020)
Background Involving patients’ representatives in the research and development of medicinal products (medicines R&D) leads to better medical treatment. In 2014, the European Patients’ Academy on Therapeutic Innovation (EUPATI) was started with the goal of increasing the capacity and capabilities of patient representatives in this field. To make this academy more accessible and applicable for the Netherlands, a Dutch version was launched in September 2019. To explore the options for a durable infrastructure for organizing the Dutch EUPATI course, a multi-stakeholder qualitative study was done. The views of various stakeholders from pharmaceutical industry, governmental organizations, patient organizations and the academic world were examined about the benefits and challenges of this course for patient involvement in medicines R&D. Methods From April to June 2019, ten semi-structured interviews were completed, each with two representatives of all stakeholders involved. In addition, individual Dutch graduates of the European EUPATI (EUPATI fellows) were consulted via an e-mail questionnaire. Using a directed content analysis based on the Business Canvas Model, the transcribed interviews were coded, analyzed, and final attributes consolidated. Results The semi-structured interviews and completed questionnaires explored how the stakeholders are aiming to assist patient involvement in medicines R&D through the Dutch EUPATI course. The building blocks of the Business Canvas Model were described with concrete attributes for making the business case. Stakeholders stated that the Dutch EUPATI course was an incentive for patient involvement in medicines development, for patient-oriented research and outcomes, for the availability of patient representatives (expert ones in particular), and for the content and representation quality of patient representatives. The key values for collaborating in the network as mentioned by the stakeholders were neutrality, patients’ interests, equality, independence, shared objectives, long-term commitment, transparency, understanding, trust, and respect. Conclusions Patient involvement in medicines R&D is evolving and the demand for qualified patient representatives is growing. Dutch stakeholders confirmed the added value of the patients’ academy and expressed their willingness to contribute. Important values and conditions for long term collaboration were formulated.